Minimum Global Tax: Winners and Losers in the Race for Mergers and Acquisitions - Vito Amendolagine; Randolph Luca Bruno; Maria Cipollina; Gianluigi De Pascale (Institute of Labor Economics (IZA), 2023)
This study aims to quantify the impact of the global minimum corporate tax rate – a pillar of the OECD's reform of international taxation – on cross-border mergers and acquisitions (M&A) involving large multinational enterprises (MNEs). First, the influence of differences in capital taxation on bilateral cross-border M&A is assessed using a structural gravity model. The resulting estimated coefficients are then applied to evaluate the impact of a 15% global minimum tax rate on cross-border investments by firms whose revenue exceeds exteuro750 million, whenever the target country's corporate tax rate is lower. The study exploits a large, disaggregated dataset of 13,562 investor-firm M&A data points from 2001 to 2020 relating to 516 industries, defined at the 4-digit level of the NACE Rev. 2 classification, in 109 'source' countries, and 559 industries (defined at the same of detail) in 161 'target' countries. The empirical results suggest that M&A flows are higher when the source and target countries have similar tax rates, while the overall effect of the global minimum corporate tax on M&A flows would be negative (as expected), but small.
Keywords: H2; H87; F23; 330; global tax rate; bilateral foreign direct investment; profit shifting; Structural Gravity model